Adenomatous Polyps in Adolescent Girl and Boy: A Report of Two Cases. (19th October 2016) - Vahedi Larijani, Laleh; Ghasemi, Maryam; Karami, Hassan
Abstract : A polyp is defined as a mass of the mucosal surface that protrudes into the lumen of the gastrointestinal tract. Neoplastic epithelial polyps are classified histologically as either benign adenoma or malignant carcinoma. The colonic polyps that most commonly present in children occur sporadically and individually and are of the juvenile type; they are most frequently associated with painless rectal hemorrhage (which is the most common symptom). Adenomatous polyps are similar to other nontumoral polyps, and it is very rare for children to have symptoms other than rectal bleeding. This report describes two rare cases of polyps in pediatric patients. An 11-year-old girl presented with tubulovillous adenoma and a 13-year-old boy with tubular adenoma; both patients complained of rectal hemorrhage as well as anemia and abdominal pain. Epithelial adenoma is a tumor that is rarely found in adults or children. Colonoscopic perforation and biopsy are mandatory for establishing a definitive diagnosis and avoiding medical mismanagement.